Interchangeable drugs in Peru. A review study - Ericson Félix Castillo Saavedra; Franklin Jhony Julián Méndez; Verónica Yamilet Coronel Vega; Cecilia Elizabeth Reyes Alfaro; Rosa María Salas Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
The medicines' interchangeability represents a necessity in developing countries, because it offers the possibility of accessing lower cost products, it allows to ensure efficacy and safety in pharmacotherapeutic treatments. The study gather researches carried out in the Peruvian state published in high-impact databases such as Scielo, Sciencedirect, Scopus and Pubmed. Of the 553 researches found, only 10 articles met the inclusion and exclusion criteria, drugs such as diazepam, prednisone, amoxicillin, doxycycline, fluconazole, phenytoin sodium, alprazolam, amlodipine, carbamazepine sodium, glibenclamide, moxifloxacin and acetylsalicylic acid were identified. All the articles analyzed the dissolution profile by calculating the similarity factor f2, while, in other cases, they estimated parameters such as weight variation, friability, hardness, quantification, content uniformity, and dissolution profile. The results show that 9 drugs included in the study were analyzed by in vitro studies at different pH (1.2; 4.5 and 6.8), and complied with presenting a similarity factor f2 greater than 50. It is concluded that, the interchangeability of medicines in the Peruvian state is still in process, and that, through strategic alliances with the private sector, a greater number of pharmaceutical alternatives could be had in the patient's recovery.